Synthesis and physico-chemical investigation of vanadium phosphorus oxide catalysts derived from VO(H2PO4)2 - Yap, Taufiq Yun Hin; Goh, Chee Keong (Universiti Putra Malaysia Press, 2003)
Vanadium phosphorus oxide catalysts were prepared via VO(H2P04)2 by using two methods: i) reaction of V204 with σ-H3P04 and ii) reduction of VOP04.2H2O with octan-3-ol. The precursors were calcined in n-butane/air mixture at 673 K for 75 h. These catalysts were characterised by using various techniques, such as BET surface area, XRD, FTIR and SEM.